Laser brazing with beam scanning: Experimental and simulative analysis - Heitmanek, Marco; Dobler, Michael; Graudenz, Matthias; Perret, William; Göbel, Gunther; Schmidt, Michael; Beyer, Eckhard (International Conference on Laser Assisted Net Shape Engineering, LANE 2014, 2014)
Laser beam brazing with copper based filler wire is a widely established technology for joining zinc-coated steel plates in the body-shop. Successful applications are the divided tailgate or the zero-gap joint, which represents the joint between the side panel and the roof-top of the body-in-white. These joints are in direct view to the customer, and therefore have to fulfil highest optical quality requirements. For this reason a stable and efficient laser brazing process is essential. In this paper the current results on quality improvement due to one dimensional laser beam deflections in feed direction are presented. Additionally to the experimental results a transient three-dimensional simulation model for the laser beam brazing process is taken into account. With this model the influence of scanning parameters on filler wire temperature and melt pool characteristics is analyzed. The theoretical predictions are in good accordance with the experimental results. They show that the beam scanning approach is a very promising method to increase process stability and seam quality.
Keywords: Joint quality; Laser brazing; Laser brazing simulation; Zero-gap joint; Zinc-coated steel plate